THE DEVELOPMENT OF ENTREPRENEURSHIP LEARNING MODEL BASED ON THE CONTEXTUAL IN THE UNIVERSITY - Wesnita, Alvia (Ensiklopedia Sosial Review, 2019)
The aims of this development research is to produce entrepreneurship learning model based onthe valid contextual, practical and effective.The research follows the design of model of the Branch (2009). There are five steps from the design model of the Branch (2009), namely; analysis, design, development, implementation and evaluation (ADDIE). To collect the data, the instrument that writer used are the observation, instrument validation and test sheets. To validate instrument products, expert assessment of the strategies are chosen by using the delphi technique and continued with exploration of the feasibility which is applied by using focus group discussions technique. The data will be analyzed through qualitative and quantitative techniques. In order to get the book of entrepreneurship learning model and the guidebook based on the contextual, the data were analyzed by using qualitative and quantitative methods. The validity of the product are tested by expert, the practical test by the user, and the effectiveness test trought the students learning outcomes. The results of the development consists of (1) book-entrepreneurship learning model based on contextual, (2) the lecturers’ guidebook of entrepreneurship learningmodel based on contextual, (3) Student Handbook learning model based on contextual is valid, practical and effective.